Sorption and desorption of inorganic phosphate by soils as influenced by inorganic and organic anions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science (Soil Science) at Massey University - Earl, Keith David (Massey University, 1975)
Anions play a very significant role in the retention and plant availability of soil and fertilizer inorganic phosphate (P). Evidence that different inorganic and organic anions can modify P retention was presented by many workers prior to 1950 ( Kurtz et al., 1946; Dean and Rubins, 1947; Swenson et al., 1949 ). The exact mechanisms of this effect was little understood. In addition, a range of chemical extractants have been used to assess the available P status of soils; these included citrate, tartrate, fluoride, arsenate, and other anions capable of forming stable complexes with Fe and Al in soils. It is now well recognised that microorganisms and root excretions greatly modify the chemical environment in the rhizosphere. Organic compounds found in the root exudates of several plants ( reviewed by Rovira, 1965 ), and produced by microorganisms, include many organic acids known to form strong complexes with metal ions. Such compounds may be an important factor affecting the mobility of P in soils. [FROM INTRODUCTION]
Keywords: Phosphates